URGENSI ANALYSIS KEBUTUHAN (NEED ANALYSIS) PADA MATA KULIAH ESP (English For Specific Purposes) PADA MAHASISWA SISTEM INFORMASI STMIK IN PEKANBARU - Nurul Mahfuza; Agung Setiabudi (Yayasan Pelita Negri Belantaraya, Kab. Indragiri Hilir, Prov. Riau, 2024)
The achievement of learning English for Specific Purposes (ESP) in the Information Systems Department of the Indragiri Pekanbaru College of Information Management and Computer Science is considered less than optimal. Many alumni, even though they have mastered the field of science and profession very well in the field of computer science, can be said to be less than optimal in terms of communicating using English, both verbally and non-verbally in their field of work. One of the causes is the less than optimal learning planning where the material provided is often not in accordance with the field of science taught by students. In this regard, a learning plan is needed that begins with carrying out a needs analysis of English learning materials with specific purposes (ESP). This study uses a survey method in the form of a structured questionnaire that is closed-ended to obtain qualitative data on respondents, namely; students majoring in information systems semester 3 of the Indragiri Pekanbaru College of Information Management and Computer Science. From the data obtained, a summary of important English learning materials has been found, covering 4 areas of language skills and language topics that are relevant to the fields of science and work of students majoring in information systems. The results of the study revealed that a needs analysis is needed to determine the level of student learning and the relevant materials that they have mastered in the ESP course, in addition, needs analysis also helps lecturers in making RPS, choosing teaching materials that are relevant to student needs in order to achieve effective learning. The results of this study are also expected to be used as reference material for further research, namely syllabus/RPS planning and development of English teaching materials for other departments that are considered to have to have English communication skills. Keywords: Need analysis, English for specific purposes (ESP), English information systems, RPS.